PENGERINGAN GABAH DENGAN MENGGUNAKAN PENGERING RESIRKULASI KONTINYU TIPE KONVEYOR PNEUMATIK - Ivan Aditya Gunawan; Aulia Rahman Majid; Siswo Sumardiono (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Rice is one of the most important food commodities in the world. So we need to handle it seriously to reduce loss due to improper post-harvest handling. One of the post-harvest handling that noteworthy is the paddy grain drying process. Paddy grain drying process by conventional methods are often encounter many obstacles and no longer relevant to use. Therefore, required an innovative drying tool as an alternative to paddy grain drying.Recirculating paddy grain dryers with pneumatic conveyor could be an alternative, because it has several advantages that good quality dried grain and uniform, and easy to perform control during the drying process. The purpose of this study was to determine the effect of temperature and velocity of pneumatic air to the drying rate. The variables studied in this research isthe velocity of pneumatic airflow, and temperature of drying air. From the research we got that it will be running effectively at a temperature of 60 ° C and pneumatic air velocity of 20 m / s.